Microbial Ecology of Permafrost Soils: Populations, Processes, and Perspectives - Waldrop, Mark P.; Ernakovich, Jessica Gilman; Vishnivetskaya, Tatiana A.; Schaefer, Sean R.; Mackelprang, Rachel; Barta, Jiri; O′Brien, Joy M.; Winkel, Matthias; Barbato, Robyn A.; Heffernan, Liam; Leewis, Mary‐Cathrine; Hewitt, Rebecca E.; et al. (John Wiley & Sons, 2025)
Permafrost microbial research has flourished in the past decades, due in part to improvements in sampling and molecular techniques, but also the increased focus on the permafrost greenhouse gas feedback to climate change and other ecological processes in high latitude and alpine permafrost soils. Permafrost microorganisms are adapted to these extreme environments and remain active at low temperatures and when resources are limited. They are also an important component of global elemental cycles as they regulate organic matter turnover and greenhouse gas production, particularly as permafrost thaws. Here we review the permafrost microbiology literature coupled with an exploration of its historical aspects, with a particular focus on a new understanding advanced by molecular biology techniques. We further identify knowledge gaps and ways forward to improve our understanding of microbial contributions to ecosystem biogeochemistry of permafrost-affected systems.
Keywords: permafrost soils; microbial ecology; climate changes